India’s Growth Strategy Through NITI Aayog - KUMAR, DR. P. PRAVEEN; MR. NAGARAJAN. S, (The journal of contemporary issues in business and government, 2020)
The NITI Aayog was implemented to carry new plans. Its first order is to go about as a research organization. It is well known as a bridge through which new and imaginative thoughts occur from a single imaginable source - industry, the scholarly world, common society, or unfamiliar authorities and stream into the administration framework for usage. It has customary meetings to generate new ideas with partners from different ventures and areas. We distinguish the prescribed procedures in various states in different areas and afterward attempt to imitate them in different states. The information is then utilized at the most noteworthy policymaking levels to set up responsibility and improve execution. This exhibition and result based ongoing observing and assessment of government work can significantly affect improving the proficiency of administration. There's a need to legitimize direct charges for both corporate expense and individual annual duty, facilitating the assessment consistency trouble which alongside demonetization and GST will support India's expense to GDP proportion. Utilizing such information, additionally concoct execution-based rankings of States across different verticals to cultivate a feeling of serious federalism. Move Hack expected to achieve creative, dynamic, and adaptable answers for issues about portability. This study tries to examine whether the function of NITI Aayog is more reliable and find the perception of literate people on the functions of NITI Aayog in Chennai city.